2014
DOI: 10.1016/j.meegid.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Poxviruses and the evolution of host range and virulence

Abstract: Poxviruses as a group can infect a large number of animals. However, at the level of individual viruses, even closely related poxviruses display highly diverse host ranges and virulence. For example, variola virus, the causative agent of smallpox, is human-specific and highly virulent only to humans, whereas related cowpox viruses naturally infect a broad spectrum of animals and only cause relatively mild disease in humans. The successful replication of poxviruses depends on their effective manipulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
267
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(278 citation statements)
references
References 252 publications
(451 reference statements)
3
267
0
8
Order By: Relevance
“…The numerous viral genes devoted to host interactions provide a living record of the natural selection that has occurred over millennia. Indeed, such genes constitute approximately half of the large DNA genomes of poxviruses (2,3). In general, the defense genes can be recognized by their location near the ends of the genome and their variability compared with the ∼100 genes highly conserved in all vertebrate poxviruses that are needed for replication and dissemination (4).…”
mentioning
confidence: 99%
“…The numerous viral genes devoted to host interactions provide a living record of the natural selection that has occurred over millennia. Indeed, such genes constitute approximately half of the large DNA genomes of poxviruses (2,3). In general, the defense genes can be recognized by their location near the ends of the genome and their variability compared with the ∼100 genes highly conserved in all vertebrate poxviruses that are needed for replication and dissemination (4).…”
mentioning
confidence: 99%
“…The serological evidence of OPXV exposure indicates that several species of common African wild animals are susceptible to OPXV infection. MPXV, CPXV and VACV are also known to naturally infect very broad ranges of mammalian species (Essbauer et al, 2010;Haller et al, 2014) and CPXV infection of shrews has been reported (Laakkonen et al, 2006;Tryland et al, 1998).…”
mentioning
confidence: 99%
“…This 'host range' can be experimentally correlated with the presence of defined 'host range genes' which are commonly immunomodulators that block divergent host specific anti-viral responses [4]. These genes are under strong evolutionary selection and vary dramatically even between similar species within a genus [5].…”
Section: Poxviruses and Innate Immunitymentioning
confidence: 99%